Dissipation study and dietary risk assessment of dinotefuran, DN, and UF in wolfberry. Issue 13 (20th October 2020) - Li, Wei; Shen, Shuo; Chen, Hongyu; Guo, Qingyun
ABSTRACT: In this study, a reliable and efficient residue analytical method to determine dinotefuran and its metabolites [1-methyl-3-(tetrahydro-3-furylmethyl) guanidine (DN) and 1-methyl-3-(tetrahydro-3-furylmethyl) urea (UF)] in wolfberry and soil was established. The mean recoveries from soil and wolfberry matrices ranged from 84.7 to 98.9%, with intra-day relative standard deviations (RSDr) in the range of 0.9–2.5% for three test compounds. The limits of quantification (LOQs) were 0.005 mg kg −1 for dinotefuran, DN, and UF in wolfberry and soil matrices, and the limits of detection (LODs) were 0.0001 mg kg −1 for three compounds in two matrices. The dissipation and residual assay in 2016 with the commercial formulation of dinotefuran thiamethoxam 30% suspension concentrate (SC) was conducted at four locations of Qinghai, Gansu, Inner Mongolia, and Ningxia province. The dissipation rates of dinotefuran were rapid in wolfberry with the half-lives were 1.4–3.1 days. The dissipation in soil were relatively slow with half-lives 7.5–17.4 days. According to the results of dietary risk assessment, the residue of dinotefuran at the recommended dosage is safe for human